STRATEGI RESPONS KRISIS KORPORASI DALAM PRESPEKTIF TEORI PEMULIHAN CITRA : ANALISIS KUANTITATIF KASUS ETILEN OKSIDA PT. INDOFOOD - Maritza Salsabila Fathihana; Dian Purworini (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
When an institution faces a significant and unexpected threat to its operations, reputation, or longevity and requires swift action to control public opinion, a communication crisis occurs. This crisis can be caused by internal factors (bad policies, defective products) or external factors (bad press, natural disasters, cyberattacks). This study aims to analyze two cases of ethylene oxide (EtO) content that occurred at Indofood in 2023 and 2025. This study uses a quantitative descriptive approach with a content analysis method. Sampling was carried out using a purposive sampling technique. The unit of analysis was a paragraph with a total of 32 paragraphs coded into five IRT strategy categories: Denial, Evasion of Responsibility, Reducing Offensiveness, Corrective Action, and Mortification. The results show that the most dominant strategy used in both crisis periods was Corrective Action (42.3%), followed by Minimization and Bolstering as part of Reducing Offensiveness. In dealing with the [A1.1]crisis, Indofood carried out stricter quality control of raw materials throughout the global supply chain, emphasized the safety of their products through certification, and implemented stable and consistent communication patterns. Keywords: Indofood, Crisis, Food Security, Image Repair Theory